2013
DOI: 10.1159/000350479
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Human Studies to Estimate Anticaries Efficacy of Fluoride Toothpastes

Abstract: Much more than mechanical biofilm removal, toothbrushing with fluoride toothpastes is an effective way of increasing the availability of fluoride in the oral cavity to reduce demineralization and enhance remineralization of enamel and dentine. These effects of fluoride toothpastes have been estimated by a wide range of laboratory and human studies, which have helped to develop anticaries effective formulations and understand their mechanism of action. These studies have focused on the availability of fluoride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 128 publications
(144 reference statements)
3
68
0
12
Order By: Relevance
“…Any model has limitations to adequately simulate the in vivo conditions (19). The use of bovine enamel as a surrogate of human enamel can be considered acceptable given that similar reactivity with both of them has been observed after the use of professional fluoride products (4,6).…”
Section: Fluoride Varnish Reaction Is Time-dependentmentioning
confidence: 99%
“…Any model has limitations to adequately simulate the in vivo conditions (19). The use of bovine enamel as a surrogate of human enamel can be considered acceptable given that similar reactivity with both of them has been observed after the use of professional fluoride products (4,6).…”
Section: Fluoride Varnish Reaction Is Time-dependentmentioning
confidence: 99%
“…The reactivity of fluoride from dentifrices with the tooth surface is also considered as a mode of action of FD [Tenuta and Cury, 2013]. In our study, for all studied conditions, the CaF 2 and FAp concentrations varied directly according to the frequency of FD ( fig.…”
Section: Discussionmentioning
confidence: 93%
“…© 2016 S. Karger AG, Basel Fluoride dentifrice (FD) is the most rational way to use fluoride [Fejerskov et al, 2015] and the caries decline observed in developed countries after the 1980s [Bratthall et al, 1996] and in some developing countries after the 1990s [Cury et al, 2004] has been attributed to the widespread use of FD. The mechanisms by which FD controls dental caries were recently reviewed [Tenuta and Cury, 2013]. FD is able not only to reduce caries progression on sound enamel-dentine surfaces ('preventive effect'), but also able to remineralize preexisting caries lesions ('therapeutic effect').…”
mentioning
confidence: 99%
“…Evidence has demonstrated that modern fluoridated toothpastes, including among others either NaF-or SnF 2 -based toothpastes, are effective at controlling dental car-ies [Walsh et al, 2010] because of fluoride's activity in reducing demineralization and enhancing remineralization [ten Cate, 2013;Tenuta and Cury, 2013]. Beside the caries control effect, SnF 2 -containing toothpastes have been reported to reduce dental plaque [Sharma et al, 2013], bleeding [Gerlach and Amini, 2012], halitosis [Farrell et al, 2008], erosion [Bellamy et al, 2014] and dentin hypersensitivity [Parkinson et al, 2013].…”
mentioning
confidence: 99%